Clinical photography: Attitudes among dental students in two dental institutions. (19th February 2019) - Czerninski, Rakefet; Zaidman, Brooke; Keshet, Naama; Hamburger, John; Zini, Avraham
Abstract: Introduction: Clinical photography is an important tool in teaching, clinical practice and academia especially for mucosal pathologies. Our aim was to examine differences in attitude towards clinical photography for mucosal pathologies among students. Methods: Questionnaires about clinical photography were completed by students in dental teaching hospitals in Birmingham (UK) and in Israel (ISR). The questionnaires focussed on the perceived value of clinical photography for a number of purposes and also explored perceived barriers to clinical photography and technology in general. The two departments have different access to clinical photography; in the United Kingdom a separate dedicated photography unit takes all the photographs, whereas in ISR the clinicians take their own photographs. Pearson Chi‐squared tests determined statistical significance between categorical variables ( P < 0.05). Results: Among the 163 respondents, there were no significant differences in the value of photography between countries or genders. The participants felt that the aims of photography included: teaching (99.4%), monitoring premalignancy (97.6%) and clinician communication (95.8%). More than 90% thought photography should be used for dysplasia and erosive lichen planus cases. Respondents from ISR were more in favour of photographing pathologies including simple leukoplakia, reticular lichen planus, vesiculobullous or pigmented lesions ( P < 0.001 compared to the UK). Overall, the main reasons for not using photography were time constraints (25.5%) and access (21.8%). Conclusions: This study highlights a favourable attitude towards clinical photography for various teaching and clinical indications thereby demonstrating its importance. In order to maximise the benefits of clinical photography, access should be simplified.